The analysis of the canid mitochondrial genome studied in Morocco shows that it is neither wolf (Canis lupus) nor Eurasian jackal (Canis aureus) - Urios Moliner,Vicente; Donat-Torres,Maria P; Ramírez Castillo,Carlos A; Monroy-Vilchis,Octavio; Rguibi Idrissi,Hamid (PeerJ PrePrints, 2016)
The mitochondrial genome of three Moroccan canids has been analysed. Two of them complete and one partial. The sequences are included in GenBank with the accession number KT378605 (16721 bp), KT378606 (16734bp) and KT378607 (27809bp) Theses results have been compared with the results currently available in GenBank. In the phylogenetic analysis of the of cytochrome b regions and control region the three are grouped together with Canis lupus lupaster and the Senegalese golden jackal Canis aureus and separate from the wolf Canis lupus and the Eurasian golden jackal Canis aureus. The comparison of the complete mitochondrial genomes with Canis lupus confirms the distance between the two groups. We conclude that they belong to a different species to the wolf Canis lupus and the Eurasian golden jackal. We propose in agreement with (Koepfli et al., 2015) that it´s scientific name be Canis anthus by merit of being the name by which it was classified and published for the first time as a different species by Cuvier in 1824. The preprint is a translation of a Spanish document published in Altorero journal on the 15th August 2015.
Keywords: Canis anthus; Canis aureus lupaster; Canis lupaster; complete mitochondrial genome; North African jackal; Canis lupus lupaster; Morocco